Desain Karakter Untuk Media Edukasi Skateboard Di Kota Surabaya - Ricko Gohans Putra; Aris Sutejo; Aryo Bayu Wibisono (CITRAKARA, 2026)
This study aims to design character visuals as a visual medium for an educational skateboarding book for beginners aged 18–21 in Surabaya. The research is motivated by the increasing interest of young people in skateboarding that has not been accompanied by adequate understanding of basic techniques, safety, and playing ethics. Questionnaire data from 264 respondents indicate that most are interested in learning skateboarding and prefer visually based learning media. The method used is Three Dimensional Development, a character development approach that considers physiological, psychological, and sociological aspects to create characters with strong visual and narrative identities. The design results show that the use of illustrative characters can enhance teenagers’ interest in educational books, facilitate material comprehension, and support a more effective and communicative learning process. The design stages include brainstorming, sketching, lining, and coloring toproduce consistent characters aligned with audience preferences. In conclusion, character design is effectively used as an alternative educational medium that is informative, engaging, and relevant to the characteristics of young audiences.